An approach for failure prediction in H3 TRB-tests - Kolbinger, Elisabeth; Wuest, Felix; Dijk, Marius van; Trampert, Stefan; Lang, Klaus-Dieter (2019 22nd European Microelectronics and Packaging Conference & Exhibition (EMPC), 2019)
Applications for power modules under harsh environmental conditions have gained importance in recent years, e.g. in offshore wind turbines. One of the critical conditions that leads to failures in these applications is humidity. Therefore, it is important to subject the power electronics to appropriate load tests in advance, in order to generate these failures. An established test method for the qualification of power electronics is the High Humidity High Temperature Reverse Bias (H 3 TRB)-test. This paper deals with the prediction of failures in H 3 TRB-tests. The goal in this paper is to use the currents noise to improve the method of forecasting time to failure in H 3 TRB-testing. This is based on the assumption that there may be a correlation between the time to failure and the point in time at which the electrical parameters begin fluctuating.